2016
DOI: 10.1016/j.atmosenv.2016.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the ice nucleating abilities of marine aerosol: A combination of deposition mode laboratory and field measurements

Abstract: 23 This study addresses, through two types of experiments, the potential for the oceans to act as a 24 source of atmospheric ice-nucleating particles (INPs). The INP concentration via deposition 25 mode nucleation was measured in situ at a coastal site in British Columbia in August 2013. The 26 INP concentration at conditions relevant to cirrus clouds (i.e., -40°C and relative humidity with 27 respect to ice, RHice=139%) ranged from 0.2 L -1 to 3.3 L -1 . Correlations of the INP 28 concentrations with levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
122
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(140 citation statements)
references
References 64 publications
15
122
1
Order By: Relevance
“…An identical chamber (Kanji and Abbatt, 2009) has been used for online field studies (Ladino et al, 2016) and processing of resuspended field samples (Wilson et al, 2015) at 233 K and water-subsaturated conditions. Here we compare results from two field campaigns in winter 2015 and 2016 to previously conducted INP measurements in the same season with PINC (Boose et al, 2016a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An identical chamber (Kanji and Abbatt, 2009) has been used for online field studies (Ladino et al, 2016) and processing of resuspended field samples (Wilson et al, 2015) at 233 K and water-subsaturated conditions. Here we compare results from two field campaigns in winter 2015 and 2016 to previously conducted INP measurements in the same season with PINC (Boose et al, 2016a).…”
Section: Resultsmentioning
confidence: 99%
“…Recent field studies or studies of field samples in the laboratory (Cziczo et al, 2013;Knopf et al, 2014;Wilson et al, 2015;Ladino et al, 2016;DeMott et al, 2016) have shown that particles and organic matter sampled or emitted from the sea surface can be a source of INPs. Marine aerosols are produced via a bubblebursting mechanism (e.g., de Leeuw et al, 2011;Gantt and Meskhidze, 2013;Aller et al, 2005;Cunliffe et al, 2013) when entrained air bubbles rise through the sea surface microlayer and burst upon contact with the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the suggestion that whole cells are not the source of the INPs. Potential sources of the INPs observed in this study include ultramicrobacteria, viruses, phytoplankton exudates, or bacteria exudates (Ladino et al, 2016;Wilson et al, 2015).…”
Section: Size Of Inpsmentioning
confidence: 99%
“…More recently INP of marine origin, those associated with marine biological activity and sea spray production, have seen a resurgence in interest as well (e.g. Després et al, 2012;Burrows et al, 2013; Wilson et al, 2015;DeMott et al, 2016;Ladino et al, 2016; McCluskey et al, 2017). Perhaps the most well-known INP species, primarily so due to its size, morphology, significant presence in the atmosphere and the ability to be transported great distances, is 30 mineral dust (e.g.…”
mentioning
confidence: 99%